PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PERKEBUNAN KELAPA SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mario Winaldi Pratama; Iqbal, Johandri; Saputra, Ferdyan Wana (Journal of Applied Accounting And Business, 2025)
This research aims to analyze the effect of profitability and leverage on tax avoidance in palm oil plantation sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Using a quantitative approach, this research collects secondary data in the form of company financial reports. The sampling method used was purposive sampling, to obtain a representative sample. With 7 companies and 5 year financial reporting periods, using ROA, DER and ETR indicators. Data analysis was carried out using classic assumption tests, including normality, multicollinearity, heteroscedasticity and autocorrelation tests to ensure the accuracy of the regression model used. The results of the research show that there is a significant relationship between profitability and leverage on tax avoidance, which indicates that profits and debt can influence the tax burden. High leverage will affect profits, indicating that the company has low tax avoidance. These findings provide important insights for stakeholders in understanding the factors that influence tax avoidance in the palm oil plantation sector.